KEPATUHAN IBU HAMIL MENGKONSUMSI TABLET FE (Studi Kasus Suku Bajo Kota Kendari Tahun 2020) - Riskilia Antista; La Ode Muhamad Sety; Jusniar Rusli Afa (Endemis Journal, 2021)
Fe tablets are mineral tablets that the body needs for the formation of red blood cells. Fe tablets are very important for pregnant women because they have functions such as increasing the intake of nutrients in the fetus and preventing anemia. Compliance with pregnant women to consume Fe tablets is the behavior of mothers in consuming Fe tablets regularly. The purpose of this study was to find out more about the compliance of pregnant women in consuming Fe tablets in the Bajo tribe in the work area of the Mata Puskesmas, Kessilampe Village, Kendari City. This type of research is a qualitative descriptive study with data collection techniques through interviews and observations to find out more about maternal compliance in consuming Fe tablets. The subjects of this study were 5 pregnant women who were key informants. Retrieval of data sources on informants was carried out by purposive sampling, namely sampling techniques with certain considerations, namely that the data source is considered to know best about what is expected so that it makes it easier for researchers to explore the object under study. The results showed that most of the pregnant women of the Bajo tribe in the work area of the Eye Health Center were obedient to consuming Fe tablets regularly, and there was a close relationship between maternal compliance in consuming Fe tablets with knowledge, motivation, and family support of pregnant women. Positive behavior in pregnant women will have an impact on obedient actions in consuming Fe tablets, if pregnant women have good knowledge about the importance of Fe tablets, pregnant women will be more obedient to consume them and pregnant women also need to motivate themselves and get support from their closest family in particular. husbands to be more obedient in consuming Fe tablets.